2010
DOI: 10.1007/s11906-010-0091-9
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Renin-Angiotensin Blockade: Angiotensin-Converting Enzyme Inhibitors as the Starting Point

Abstract: The renin-angiotensin system has been a target in the treatment of hypertension for close to three decades. Several medication classes that block specific aspects of this system have emerged as useful therapies, including angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and, most recently, direct renin inhibitors. There has been a natural history to the development of each of these three drug classes, starting with their use as antihypertensive agents; thereafter, in each case they have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Recently, it has been suggested that there may be an overreliance on the Ang II model considering that the model is not reflective of primary (essential) hypertension, which accounts for the majority of hypertension in humans (Galis et al, 2013 ). While the Ang II infusion model is most reflective of secondary forms of hypertension, it should be noted that a major target of antihypertensive therapy in essential hypertension in humans has been directed toward limiting Ang II signaling (e.g., ACE inhibitors and angiotensin receptor blockers) (Sica, 2010 ; Hanselin et al, 2011 ). Thus, the Ang II infusion model clearly has direct relevance to human hypertension irrespective of etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been suggested that there may be an overreliance on the Ang II model considering that the model is not reflective of primary (essential) hypertension, which accounts for the majority of hypertension in humans (Galis et al, 2013 ). While the Ang II infusion model is most reflective of secondary forms of hypertension, it should be noted that a major target of antihypertensive therapy in essential hypertension in humans has been directed toward limiting Ang II signaling (e.g., ACE inhibitors and angiotensin receptor blockers) (Sica, 2010 ; Hanselin et al, 2011 ). Thus, the Ang II infusion model clearly has direct relevance to human hypertension irrespective of etiology.…”
Section: Introductionmentioning
confidence: 99%
“…to treat renal fibrosis in the clinic, but efforts have been made to intervene in the primary disease (Li et al 2018). The main clinical treatment for most forms of kidney disease is angiotensin inhibition (Sica 2010). Therefore, it is urgent to develop novel drugs that can treat or delay renal fibrosis.…”
Section: Aip Inhibits Emt Progression In Vivo and In Vitromentioning
confidence: 99%
“…Oral ACE inhibitors, the oldest category of RAAS inhibitor, were commercially released over thirty years ago in the early 1980s, over a decade before the first ARBs became available 5 . The introduction of ACE inhibitors heralded major changes in the way hypertension and cardiovascular disease were treated.…”
Section: Introductionmentioning
confidence: 99%